Impact of different mating ratios of broiler breeder on reproductive performance during post moult phase - Mohammad A. Elsagheer; Omar A. Mohamed; Ibrahim M. Khattab; Marian K. Wadea (Animal Biotechnology, 2024)
Studies comparing mating ratio after forced molting are important for improving the efficiency of broiler breeder flocks. This study examined the effect of mating ratios on Egg production, chick weight, fertility, hatchability and embryonic mortality rate in Arbor Acres Plus broiler breeders post-moult phase. A total of 195 birds (62 weeks old), consisting of 15 cocks and 180 hens were randomly allocated with uniform body weight in a Completely Randomized Design into three groups based on the mating ratio (cock to hen). The groups included ratios of 1:10, 1:12, and 1:14, with each group replicated 5 times. Eggs were collected twice a day, and stored for 7 days at room temperature before placing them in the incubator. Results showed that mating ratios 1:10 and 1:12 had a positive effect on fertility rate and total hatchability compared to the 1:14 ratio. However, mating ratios did not affect laying rate, egg weight, egg mass, chick weight, hatchability of fertile eggs, and embryonic mortality rate. In conclusion, to reduce the cost of raising and caring cocks, a mating ratio of one cock to every twelve hens can be used for broiler breeders after forced molting to obtain the best fertility and hatching results.